Transient Global Amnesia Associated with a Unilateral Infarction of the Fornix: Case Report and Review of the Literature - Gupta, Mihir; Kantor, Molly A.; Tung, Christie E.; Zhang, Niushen; Albers, Gregory W. (Frontiers in Neurology, 2015)
Stroke is an extremely uncommon cause of transient global amnesia. Unilateral lesions of the fornix rarely cause amnesia and have not previously been reported to be associated with the distinctive amnesic picture of transient global amnesia. We describe the case of a 60-year-old woman who presented with acute onset, recent retrograde and anterograde amnesia characteristic of transient global amnesia. Serial magnetic resonance imaging showed a persistent focal infarction of the body and left column of the fornix, without acute lesions in the hippocampus or other structures. Amnesia resolved in 6 hours. Infarction of the fornix should thus be included in the differential diagnosis of transient global amnesia, as it changes the management of this otherwise self-limited syndrome.